Pengaruh Temperatur Operasi Dan Kecepatan Superfisial Terhadap Komposisi Gas Produser Pada Gasifikasi Fluidized Bed Berbahan Bakar Sampah Terapung - Suprapta Winaya, I Nyoman; Sucipta, Made; Susila, I Dewa Made (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011)
Management of waste into energy that is economically possible with fluidized bed gasification technology. Gasification is athermo-chemical process that converts biomass/solid waste into producer gas (CO, H2, CO2 and HC) by using air, steam, oxygenor its mixtures as a gasification agent. In a study of floating waste fuel gasification in pellet form with 1,25 cm diameter and 1.25cm height and of 1.22 gram mass, where is used oxygen enriched air as gasification agent. The operating temperature (Top) atreactor selected 500oC and 600oC with superficial velocities (Uo) are 0.105 m/sec, 0.125 m/sec, 0,145 m/sec., and 0,165 m/sec.From the research results showed that by increasing the operating temperature of 500oC to 600oC and increasing the superficialvelocity of 0.105 m/sec to 0.125 m/sec, did not influence directly the increasing of percentage/levels of CO, CO2 and HC gas thatproduced.
Keywords: fluidized bed gasification, floating waste, gasification agent, producer gas, superficial velocity